Robust and tunable itinerant ferromagnetism at the silicon surface of the antiferromagnet GdRh2Si2 - Güttler, M.; Generalov, A.; Otrokov, M. M.; Kummer, K.; Kliemt, K.; Fedorov, A.; Chikina, A.; Danzenbächer, S.; Schulz, S.; Chulkov, E. V.; Koroteev, Yu. M.; Caroca-Canales, N.; et al. (Scientific reports, 2016)
Spin-polarized two-dimensional electron states (2DESs) at surfaces and interfaces of magnetically active materials attract immense interest because of the idea of exploiting fermion spins rather than charge in next generation electronics. Applying angle-resolved photoelectron spectroscopy, we show that the silicon surface of GdRh 2 Si 2 bears two distinct 2DESs, one being a Shockley surface state and the other a Dirac surface resonance. Both are subject to strong exchange interaction with the ordered 4 f -moments lying underneath the Si-Rh-Si trilayer. The spin degeneracy of the Shockley state breaks down below ~90 K and the splitting of the resulting subbands saturates upon cooling at values as high as ~185 meV. The spin splitting of the Dirac state becomes clearly visible around ~60 K, reaching a maximum of ~70 meV. An abrupt increase of surface magnetization at around the same temperature suggests that the Dirac state contributes significantly to the magnetic properties at the Si surface. We also show the possibility to tune the properties of 2DESs by depositing alkali metal atoms. The unique temperature-dependent ferromagnetic properties of the Si-terminated surface in GdRh 2 Si 2 could be exploited when combined with functional adlayers deposited on top for which novel phenomena related to magnetism can be anticipated.